Kewenangan dan Hukum Administrasi Negara: Implementasi Peraturan Daerah Nomor 1 Tahun 2019 Tentang Retribusi Jasa Umum dalam Pengelolaan Retribusi Pasar di Pasar Raya Padang - Lathifah, Hilma; Frinaldi, Aldri (AHKAM, 2023)
The objective of this article is to elucidate the role of state administrative law in the execution of regional regulation number one of 2019 pertaining to public service fees as they relate to the administration of market fees at the Padang supermarket. In accordance with regional regulations of Padang City, market service users are obligated to pay market fees. Collections are applicable to the padang raya market's market facilities, which include courtyards, stone tables, kiosks, and open areas. In accordance with the law, collection is the transfer of private sector wealth to the public sector in order to finance daily government operations and expenditures. The local government administers the collection of market levies via the commerce department. The study employs qualitative descriptive research methods. The process of selecting informants was purposeful in order to identify critical informants; snowball sampling techniques were then utilized to obtain additional informants. In implementing regional regulation number one of 2019 regarding public service levies, the Padang City Trade Department has been unable to provide maximal services, according to the findings of this study. Based on the assessment of resource indicators, it is evident that internal constraints exist in the form of resource scarcity. Conversely, external constraints are evident in the lack of public awareness regarding the obligation to pay market levies, which leads to market levies falling behind schedule and the inability to meet annual objectives.